Analisa Suku Bunga Dan Nilai Jaminan Terhadap Resiko Kredit KPR - Gustaman, Muhamad; Rahardjo, Bambang (LPPM Institut Bisnis dan Informatika Kesatuan, 2018)
Credit risk is the inability of the customer to pay installments on time or due. This study aims to determine the effect of interest rates and the total value of collateral, on the risk of bad credit. Data obtained from published financial statements published by IDX with the period of 2013 to 2017. The sampling technique used in this study was purposive sampling. The number of samples is 4 banking companies listed on the Indonesia Stock Exchange. The analytical method used in this study is multiple linear regression, correlation, and coefficient of determination to obtain a comprehensive picture of the relationship between variables one with other variables. Based on testing the hypothesis by using the statistical t-test and the F test results showed that the interest rate has no effect and is not significant to bad credit, while the guarantee value has a positive and significant effect on bad credit and simultaneously there is a significant influence of interest rates and collateral value on bad credit